A new species of Catocala Schrank, 1802 (Lepidoptera, Erebidae) from China - Saldaitis, Aidas; Ivinskis, Povilas; Floriani, Alessandro; Babics, János (Zootaxa, 2012)
A new species, Catocala borthi, from southwest China is described. The new species differs in appearance, genitalia and DNA from its closest known relative C. koreana Staudinger, 1892 and from the sympatric C. fulminea (Scopoli, 1763). In addition, three taxa, Catocala invasa Leech, 1900, syn. n., Catocala invasa melli Ishizuka 2001, syn. n. and Catocala fulminea tungus Ishizuka 2009, syn. n. are synonymised with Catocala fulminea fulminea (Scopoli, 1763). DNA barcodes (658 base pairs of Cytochrome Oxidase Subunit I 5’ region, COI-5P) were sequenced at the University of Guelph (see Hebert et al. 2003). Nomenclature follows Goater et al. 2003; Ishizuka 2001, 2009, 2011; Kononenko et al. 1998; Kononenko 2011; Park et al. 2006). Institutional acronyms are: AFM = Alessandro Floriani (Milan, Italy); BMNH – British Museum (Natural History), London; GBG/ZSM = Gottfried Behounek (Grafing, Germany)/Zoologische Staatssammlung, München (Germany); HNHM – Hungarian Natural History Museum (Budapest, Hungary); NRCV = Nature Research Centre (Vilnius, Lithuania).